2017
DOI: 10.1371/journal.pone.0176065
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic reconstruction of the weaning process in the archaeological population of Canímar Abajo, Cuba: A Bayesian probability mixing model approach

Abstract: The general lack of well-preserved juvenile skeletal remains from Caribbean archaeological sites has, in the past, prevented evaluations of juvenile dietary changes. Canímar Abajo (Cuba), with a large number of well-preserved juvenile and adult skeletal remains, provided a unique opportunity to fully assess juvenile paleodiets from an ancient Caribbean population. Ages for the start and the end of weaning and possible food sources used for weaning were inferred by combining the results of two Bayesian probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…Equally, however, these groups, although lacking cultigens, did have ready access to a wide range of wild plants and animals, thus leading to a wide range of choices in supplementary foods and thus the high observed variability in nitrogen and carbon stable isotope compositions. This may also have been true for the horticultural population of Canímar Abajo where, despite the availability of some cultigens (Chinique de Armas et al, , ), diets reliant on wild natural resources were still typical. Finally, intrapopulation variations in weaning behaviours have been observed in other human societies (Eerkens, Berget, & Bartelink, ; Howcroft, Eriksson, & Kerstin, ; Kwok et al, this volume; Reynard & Tuross, ; Tsutaya & Yoneda, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equally, however, these groups, although lacking cultigens, did have ready access to a wide range of wild plants and animals, thus leading to a wide range of choices in supplementary foods and thus the high observed variability in nitrogen and carbon stable isotope compositions. This may also have been true for the horticultural population of Canímar Abajo where, despite the availability of some cultigens (Chinique de Armas et al, , ), diets reliant on wild natural resources were still typical. Finally, intrapopulation variations in weaning behaviours have been observed in other human societies (Eerkens, Berget, & Bartelink, ; Howcroft, Eriksson, & Kerstin, ; Kwok et al, this volume; Reynard & Tuross, ; Tsutaya & Yoneda, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting for Canímar Abajo site (Horticulturalist group), where the adult population was highly dependent on marine resources and a diet including both C 3 and C 4 plants (Chinique de Armas et al, ). A recent Bayesian reconstruction of the age at weaning at this site suggested that only C 3 plants such as root cultigens and legumes were used to wean Canímar Abajo children (Chinique de Armas et al, ). However, a study of Canímar Abajo δ 13 C ap values would be necessary to understand the differences in δ 13 C co between nonadults and female adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…struction with Nitrogen isotope analysis (WARN) package for R, which uses Bayesian computation to model expected δ 15 N values of bone collagen for infants, based on the mean and standard deviation (SD) of δ 15 N values for females in the population (seeChinque de Armas et al, 2017;Tsutaya & Yoneda, 2013). The WARN package also generates maximum density estimations (MDEs) for age at start and end of weaning, enrichment of δ 15 N bone collagen over δ 15 N breastmilk , and average δ 15 N value of weaning foods.5 | RESULTSStable isotope results were obtained for 201 of the 202 bone collagen samples submitted, excluding one adult male (B175).…”
mentioning
confidence: 99%
“…Breastfeeding and weaning practices can be reconstructed cross‐sectionally by analyzing the isotope ratios of subadult skeletons from different ages (King et al, ; Redfern, Gowland, Millard, Powell, & Gröcke, ; Xia et al, ). Special kinds of weaning or post‐weaning food whose isotope ratios differ from an adult diet can be detected by comparing the isotope ratios between subadults and adults from the same population (Chinique de Armas et al, ; Katzenberg, Saunders, & Fitzgerald, ; Tessone, García Guraieb, Goñi, & Panarello, ). Because the increase in δ 13 C values in breastfed infants is relatively small (i.e., ~1‰: Fuller, Fuller, et al, ) but inconsistent among different populations (Tsutaya, ), carbon isotopes are usually used as an indicator of special kinds of weaning food (e.g., C 4 plants).…”
Section: Introductionmentioning
confidence: 99%